Choices of retirement age and its determinants in Sri lanka: Binary probit model approach - Jenathane, R.; Thayaparan, A. (University of Jaffna, 2020)
This study examined the factors that determining the choices of retirement age among government schoolteachers in Valikamam educational zone of Jaffna district in Sri Lanka. Primary data were gathered through structured questionnaires to select the sample during the period of 2019/ 2020 and those sample consists of 160 teachers who were selected randomly from 05 schools located in the above study area. Frequency analysis, chi- square and independent sample t – test were used to explain the basic characteristics of the teachers who chose mandatory and early retirement decisions. Frequency results showed that, 64% of them prefers to early retire whereas 36% of them prefers to retire at mandatory age. The results of chi-square implied that there is a significant association between the choices of retirement age and personal, income, family and work related characteristics in the study. Further, independent sample t – test suggested that average retirement age is differ across health conditions of the teachers and their family, availability of other income sources, status of work attachment and dual role problems. Personal, income, family and work related characteristics are taken into account in the probit model that explain the choices of retirement age decision whether they chose mandatory or early. The study found that the teachers who have health problems and poor health conditions in their family are more likely to retire early than others. Similarly, the teachers who are not facing dual problems and who don’t have other income sources, more probability to choose mandatory than their counterparts. The teachers who have more attached with their job and less unpaid responsibilities are less likely to choose early retire than other teachers. Findings of the study may help to the policy makers to proposed reforms on social security system as well as pension programs for the teachers in future.
Keywords: Choices of retirement age; mandatory retirement; Probit model; Status of dual role problems; Unpaid responsibilities